Treatment of systemic sclerosis-associated digital ulcers: recommendations of the Turkish Society for Rheumatology - Karadag, D. Temiz; Yalcinkaya, Y.; Akdogan, A.; Avanoglu, A.; Bes, C.; Birlik, A. M.; Hamuryudan, V (Clinical & Exper Rheumatology, 2023)
Objective Digital ulcers (DUs) are associated with a significant burden in systemic sclerosis (SSc) by leading to severe pain, physical disability, and reduced quality of life. This effort aimed to develop recommendations of the Turkish Society for Rheumatology (TRD) on the management of DUs associated with SSc. Methods In the first meeting held in December 2020 with the participation of a task force consisting of 23 rheumatologists the scope of the recommendations and research questions were determined. A systematic literature review was conducted by 5 fellows and results were presented to the task force during the second meeting. The Oxford system was used to determine the level of evidence. The preliminary recommendations were discussed, modified, and voted by the task force and then by members of TRD via e-mail invitation allowing personalised access to a web-based questionnaire [SurveyMonkey((R))]. Results A total of 23 recommendations under 7 main headings were formulated covering non-pharmacological measures for the prevention of DUs and pharmacological treatments including vasodilators, anti-aggregants, antibiotics, wound care, pain control, and interventions including sympathectomy, botulinum toxin, and surgery. Risk factors, poor prognostic factors, prevention of DU and adverse effects of medical treatments were reported as 4 overarching principles. Conclusion These evidence-based recommendations for the management of SSc-associated DUs were developed to provide a useful guide to all physicians who are involved in the care of patients with SSc, as well as to point out unmet needs in this field.
Keywords: systemic sclerosis; digital ulcer; treatment; recommendation